EFFICIENCY OF INPATIENT LAYOUT IN PRIVATE HOSPITAL (Case Study: Bhakti Asih Hospital, Brebes Central Java) - Wahyuningrum, Sri Hartuti; Wardhani, Mustika K. (architecture department, Engineering faculty, Universitas Diponegoro, 2020)
In the context of hospital building, inpatient care has large portion in comparasion of the other facility areas within hospitals related to efficiency, such as outpatient services, emergency room, diagnostic and especially inpatient function group services. Even though inpatient care group do not have specific requirements for detailed design and building equipment, it requires efficiency considerations related to correlation with room layout. It is expected that by considering the level of efficiency of service to patients, design can fulfill technical requirements of health and medical aspects.Â Regarding designs for district-level private hospitals, demand optimization of placement and layout of inpatient care became main topic in this research. This is related to the value of investment in building area development and types of services provided according to inpatient services class. The method used is comparative study of two (2) private hospital design to find the mind factors that most influence of optimization of inpatient layout. The results of study can be used as a guide in architectural design process for designing hospital buildings especially related to design efficiency of inpatient layout so that the building can function sustainability because of optimal service.